Website-Based Adolescent Mental Health Disorders Screening Application Design - Rahman, Irpan Ali; Nurapandi, Adi; Sundewi, Alis; Setiawan, Henri; Rahayu, Rita (Indonesian Journal of Global Health Research, 2024)
Mental health is a fundamental human right for individual, community, and socio-economic development. There are external and internal factors that can cause a person to experience mental problems. There are various factors contributing to the decline in the mental health of children and adolescents, such as economic problems, education, and the health crisis. The system used to help improve mental health is currently conventional, namely face-to-face between medical personnel and patients. This research aims to develop a "Design of a Website-Based Adolescent Mental Health Disorder Screening Application". Therefore, a web-based adolescent mental health screening application will be developed using the Self Reporting Questionnaire 29 (SRQ 29) method. This application was designed using the PHP programming language, MySQL database, and a decision-making system using the Self Reporting Questionnaire 29 (SRQ 29) method. The research method is development research. The research sampling was accidental sampling, The population and sample in this study consisted of 5 research subjects including: (1) Information systems media expert (2) Nursing subject matter expert (Nursing specialist) (3) Public health center (4) Headmaster (5) UKS supervisor/coordinator. Namely taking samples based on what was found by the researcher. This type of data collection uses primary data which is processed using interview observation techniques to obtain results related to adolescent mental health. Modeling using various existing modeling tools is the next step, if the modeling has been declared complete and by what you want to achieve, then proceed to planning until the main target is implementation. The assessment results from material experts obtained an average score of 4.8 in the "Very feasible" category and Media experts received an average score of 5 in the "very appropriate" category. Conclusion: The design of the Website-Based Adolescent Mental Health Disorder Screening Application that was developed has gone through a process of assessment, revision, and improvement from experts and has been declared suitable to be used as an application that helps simplify the process of screening for Adolescent Mental Health Disorders.